Cover Picture: Photometric Detection of Nitric Oxide Using a Dissolved Iron(III) Corrole as a Sensitizer (ChemPlusChem 7/2016). Issue 7 (1st April 2016) - Fischer, Stefan; Vestfrid, Jenya; Mahammed, Atif; Herrmann‐Westendorf, Felix; Schulz, Martin; Müller, Jürgen; Kiesewetter, Olaf; Dietzek, Benjamin; Gross, Zeev; Presselt, Martin
Abstract : The cover picture shows a human in an activity that can potentially trigger asthma or heart attacks. These attacks involve blood‐vessel contraction and are therefore typically indicated in advance by an increase in NO concentration in the exhaled air. Fundamental work on photonic sensing of NO via reversible binding to an amphiphilic iron(III) corrole complex is reported. Details are given in the Full Paper by M. Presselt et al. onpage 594 in Issue 7, 2016 (DOI:10.1002/cplu.201500553 ).